POLITICAL ORDER AND GOVERNANCE IN THE ARAB EAST: REGIONAL DYNAMICS AND THE ROLE OF SAUDI ARABIA - Nigina Kushaeva (Modern American Journals, 2025)
This article examines political order and governance in the Arab East by linking historical legacies with contemporary regional dynamics. It argues that the formation of political systems in the region resulted in governance configurations characterized by the dominance of executive authority and the central role of ruling elites, while mechanisms of political representation have often remained limited. The article highlights the enduring impact of historical patterns of state formation on contemporary political order and pays particular attention to Saudi Arabia as a key regional actor whose governance practices and reform trajectory reflect broader regional trends of political stability and institutional continuity.
Keywords: Arab East, political order, governance, state formation, regime stability, Gulf monarchies, Saudi Arabia, regional dynamics.